The Long-Term Effects of Using Phosphate-Solubilizing Bacteria and Photosynthetic Bacteria as Biofertilizers on Peanut Yield and Soil Bacteria Community - Wang, Yiming; Peng, Shuang; Hua, Qingqing; Qiu, Chongwen; Wu, Pan; Liu, Xiaoli; Lin, Xiangui (Frontiers in Microbiology, 2021)
Microbial inoculation is a promising strategy to improve crop yields and reduce the use of chemical fertilizers, thereby creating environment-friendly agriculture. In this study, the long-term (5 years) effects of a phosphate-solubilizing bacterium Burkholderia cepacia ISOP5, a purple non-sulfur bacterium Rhodopseudomonas palustris ISP-1, and a mixed inoculation of these two bacteria (MB) on peanut yield, soil microbial community structure, and microbial metabolic functions were evaluated in a field experiment. After five years of inoculation, total peanut yield with B. cepacia ISOP5, R. palustris ISP-1, and MB treatments increased by 8.1%, 12.5%, and 19.5%, respectively. The treatments also significantly promoted the absorption of N and increased the protein content in peanut seeds. Nutrient content also increased to some extent in the bacteria-inoculum-treated soil. However, bacterial community diversity and richness were not significantly affected by bacterial inoculums, and only minor changes occurred in the bacterial community composition. Functional prediction revealed that bacterial inoculums reduced the relative abundance of those genes associated with P uptake and transport as well as increased the abundance of genes associated with inorganic P solubilization and organic P mineralization. Bacterial inoculums also increased the total relative abundance of genes associated with N metabolism. In addition to developing sustainable and eco-friendly agricultural practice, crop inoculation with B. cepacia ISOP5 and R. palustris ISP-1 would improve soil fertility, enhance microbial metabolic activity, and increase crop yield.